Activation of Peroxisome Proliferator Activator Receptor β/δ Improves Endothelial Dysfunction and Protects Kidney in Murine Lupus. Issue 4 (April 2017) - Romero, Miguel; Toral, Marta; Robles-Vera, Iñaki; Sánchez, Manuel; Jiménez, Rosario; O'Valle, Francisco; Rodriguez-Nogales, Alba; Pérez-Vizcaino, Francisco; Gálvez, Julio; Duarte, Juan
Abstract : Women with systemic lupus erythematosus exhibit a high prevalence of hypertension, endothelial dysfunction, and renal injury. We tested whether GW0742, a peroxisome proliferator activator receptor β/δ (PPARβ/δ) agonist, ameliorates disease activity and cardiovascular complications in a female mouse model of lupus. Thirty-week-old NZBWF1 (lupus) and NZW/LacJ (control) mice were treated with GW0742 or with the PPARβ/δ antagonist GSK0660 plus GW0742 for 5 weeks. Blood pressure, plasma double-stranded DNA autoantibodies and cytokines, nephritis, hepatic opsonins, spleen lymphocyte populations, endothelial function, and vascular oxidative stress were compared in treated and untreated mice. GW0742 treatment reduced lupus disease activity, blood pressure, cardiac and renal hypertrophy, splenomegaly, albuminuria, and renal injury in lupus mice, but not in control. GW0742 increased hepatic opsonins mRNA levels in lupus mice and reduced the elevated T, B, Treg, and Th1 cells in spleens from lupus mice. GW0742 lowered the higher plasma concentration of proinflammatory cytokines observed in lupus mice. Aortae from lupus mice showed reduced endothelium-dependent vasodilator responses to acetylcholine and increased nicotinamide adenine dinucleotide phosphate oxidase–driven vascular reactive oxygen species production, which were normalized by GW0742 treatment. All these effects of GW0742 were inhibited by PPARβ/δ blockade with GSK0660. Pharmacological activation of PPARβ/δ reduced hypertension, endothelial dysfunction, and organ damage in severe lupus mice, which was associated with reduced plasma antidouble-stranded DNA autoantibodies and anti-inflammatory and antioxidant effects in target tissues. Our findings identify PPARβ/δ as a promising target for an alternative approach in the treatment of systemic lupus erythematosus and its associated vascular damage. Abstract : Supplemental Digital Content is available in the text.